2018
DOI: 10.1093/rpd/ncy126
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Emission From Materials Processing Lasers

Abstract: The emission of laser induced X-rays from materials processing ultra-short pulsed laser systems was measured. The absolute spectral photon fluence was determined using a thermoluminescence detector based few-channel spectrometer. The spectra at 10 cm from the laser focus were in the energy region between 2 and 25 keV with mean energies of ~4-6 keV (when weighted by fluence or directional dose equivalent) and up to 13 keV (when weighted by ambient dose equivalent). The operational quantities, H·'(0.07), H·'(3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…In accordance with the dosimetric measurements a dose rate of Ḣ � (0.07) = 10.8 Sv/h could be found for tungsten as target material at a distance of 100 mm to the laser processing spot from simultaneously recorded X-ray spectra. Similar results were presented by Behrens et al [6].…”
Section: Introductionsupporting
confidence: 92%
“…In accordance with the dosimetric measurements a dose rate of Ḣ � (0.07) = 10.8 Sv/h could be found for tungsten as target material at a distance of 100 mm to the laser processing spot from simultaneously recorded X-ray spectra. Similar results were presented by Behrens et al [6].…”
Section: Introductionsupporting
confidence: 92%
“…The results clearly showed that at irradiances well above 10 14 W/cm 2 X-ray photons with energies up to about 25 keV could be observed. These results were confirmed in [24]. Furthermore, Ḣ (0.07) dose rates exceeding 10 5 µSv/h were measured at a distance of 20 cm from the plasma.…”
Section: Introductionsupporting
confidence: 68%
“…In the literature, scaling laws are found for the hot-electron temperature in keV, determined with a variety of measurement methods, typically in the form of where c T is a constant with the unit keV/(µm 2 W/cm 2 ), λ L is the laser wavelength in micrometers, and the irradiance in the center of the incident Gaussian beam averaged over the pulse duration in W/cm 2 . The exponent s is in the range of 0.3-0.5 and varies for different experimental conditions as found in [11,24,[27][28][29][30], for example. It is seen that the hot-electron temperature only depends on the laser wavelength and the irradiance.…”
Section: Hot Electron Temperaturementioning
confidence: 88%
See 2 more Smart Citations